The Image of Region in Ordinary Language Consciousness of its Residents (on an Example of an Image of Kuzbass) - Olga Kondratyevа; Tatyana Frolovа (Психолінгвістика, 2018)
The article solves a topical problem, i.e. it develops the idea about the relevance of the psycholinguistic techniques’ usage in the image-building and branding of the regions. In particular it develops the thesis that an initial point of the region successful image’s formation is the studying of its image existing in the ordinary language consciousness of its residents and then and in the consciousness of other regions’ residents.